Ayo Menanam Sacha Inchi! Pemberdayaan Masyarakat Desa Aik Bukaq Menuju Kemandirian Ekonomi dan Pariwisata - Santi Rengganis, Baiq; Rahman Bilal, Fathur; Zulisnaeni, Lalu; Hadi, M. Irzan; Setiyorini, Setiyorini (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
Aik Bukaq Village in Central Lombok has great potential in developing the tourism sector and economic independence through community empowerment. One commodity that has high economic value and great potential is the Sacha Inchi plant (Plukenetia volubilis). This plant is known to be rich in omega-3, omega-6 and omega-9, as well as high in protein, so it has a high selling value on the global market. However, public knowledge about the cultivation and processing of Sacha Inchi is still limited. Therefore, this research aims to increase community capacity in cultivating Sacha Inchi as a first step towards economic independence and developing agro-based tourism in Aik Bukaq Village. The methods used in this program include outreach, technical cultivation training, field assistance, and counseling about the economic benefits and potential in tourism. Outreach was carried out to introduce Sacha Inchi to the community, followed by technical training which included planting, care and harvesting techniques. Field assistance is carried out regularly to ensure the correct application of techniques and monitor plant development. Apart from that, education was carried out about market opportunities and how to use Sacha Inchi as a tourist attraction that can increase tourist visits. The results of this program show an increase in community knowledge and skills in Sacha Inchi cultivation. Some people are starting to see the economic potential of this plant and are taking the initiative to develop small businesses based on Sacha Inchi. In addition, several local tourism businesses are interested in including Sacha Inchi as part of the agro tourism packages offered to tourists. Thus, community empowerment through Sacha Inchi cultivation can be a strategic step in realizing economic independence and supporting the development of sustainable tourism in Aik Bukaq Village.